Formation of nanopillars on 4H-SiC via self-masking CF4 plasma etching in a gas disharge ion source - Gines, Arnold Rey B. (National Institute of Physics, College of Science, University of the Philippines Diliman, 2013)
Silicon carbide is a promising semiconductor material with favourable properties such as wide bandgap, high radiation resistance and high electrical and chemical stability even at extreme environments. However, it emits light poorly which limits its application in optoelectronics. This study reports the fabrication of SiC nanopillars through a single etching process. 4H-SiC substrates were etched using reactive CF4 plasma species produced in a gas discharge ion source. As opposed to other methods, the technique operates at low power and does not require pre- and post-treatment processes. It is proposed that the nanopillar formation arise due to a self-masking mechanism using chromium and iron particles that occurs at the start of the etching process. Measured pillar diameters are in the range 11-56nm. The surfaces exhibit strong photoluminescence in the green region with peak at 526 nm. The luminescence might be due to band to band recombination arising from quantum confinement effect caused by the nanopillars. If found appropriate, the material could be used as basis for the fabrication of a more economic solid-state laser device.